Two mononuclear dysprosium(iii) complexes with their slow magnetic relaxation behaviors tuned by coordination geometry. Issue 44 (31st October 2019) - Yu, Shui; Chen, Zilu; Hu, Huancheng; Li, Bo; Liang, Yuning; Liu, Dongcheng; Zou, Huahong; Yao, Di; Liang, Fupei
Abstract : We report here two field-induced single-ion magnets of Dy(iii ), which present octahedral and pentagonal–bipyramidal coordination geometries, respectively, with their magnetic performances tuned by the coordination geometries of Dy(iii ). Abstract : Two mononuclear dysprosium(iii ) complexes [Dy(H3 NAP)2 Cl2 ]Cl·EtOH (1 ) and [Dy(H3 NAP)2 (H2 O)Cl2 ]Cl·−2CH3 CN·MeOH·0.5H2 O (2 ) were obtained by coordinating an in situ formed Schiff base ligand of 1, 3-bis(2-hydroxynaphthalenemethyleneamino)-propan-2-ol (H3 NAP) to the dysprosium(iii ) ion. Their Dy(iii ) centers are six and seven-coordinated in octahedral and pentagonal–bipyramidal coordination geometries, respectively. Their structural difference is caused by the additional coordinated water molecule in the equatorial positions of complex 2 in comparison with that of complex 1 . The well designed semi-rigid ligand contributes significantly to the low coordination numbers of Dy(iii ) ions in the two title complexes, as well as to their structural difference. Magnetic investigations revealed that complexes 1 and 2 are both field-induced single-ion magnets (SIMs) with their effective energy barriers being 22.9(6) and 153.9(5) K, respectively. They are typical SIM examples with their performances tuned by the coordination geometries of metal ions.